2009
DOI: 10.1158/1055-9965.epi-08-0422
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Soluble Mesothelin-Related Peptides in Malignant and Nonmalignant Asbestos-Related Pleural Disease: Relation with Past Asbestos Exposure

Abstract: Background: Malignant pleural mesothelioma (MPM) results from malignant transformation of mesothelial cells. Past asbestos exposure represents a major risk factor for MPM and other benign pleural disease. Soluble mesothelin-related peptides (SMRP) have been regarded as a promising serum biomarker for MPM. The aim of this study was to investigate serum levels of SMRP in malignant and nonmalignant asbestos-related pleural disease. Patients: Four groups of patients were investigated: group 1 composed of 48 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…This level is lower than in other studies [15,16], but is in accordance with other published data [17]. Nevertheless, SMRP concentration in the serum of subjects with past exposure to asbestos shows a wide variation according to different authors [9,18,19,20,21,22,23]. In addition, different cut-off levels for abnormality have been proposed (from 0.9 to 2.5 nmol) [14,15,17,19,24,25,26,27,28,29,30,31,32].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This level is lower than in other studies [15,16], but is in accordance with other published data [17]. Nevertheless, SMRP concentration in the serum of subjects with past exposure to asbestos shows a wide variation according to different authors [9,18,19,20,21,22,23]. In addition, different cut-off levels for abnormality have been proposed (from 0.9 to 2.5 nmol) [14,15,17,19,24,25,26,27,28,29,30,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…In particular, serum SMRP has been suggested as a candidate marker for diagnosis, response monitoring and prognosis of MPM [5,9,14,18,25,37] as well as for detecting the disease in its early stages, in conjunction with conventional methods such as chest radiology, CT and PET scanning [5,19,25]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was not feasible to discriminate healthy asbestos-exposed individuals from those with benign pleural and pulmonary disorders by using SMRP measurement. Previous studies indicated the possibility of SMRP to screen cases with pleural and lung disorders in asbestos-exposed population, although the efficiency of SMRP-based screening approach needs further investigation in prospective cohort studies [6,8,19,[26][27][28]. In these studies, few had evaluated the potential confounders influencing the value of SMRP [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicate that SMRP is a candidate molecule investigated in health surveillance of workers exposed to asbestos, and is considered as a promising biomarker useful for early diagnosis and monitoring the progress of ARDs [4][5][6][7]. Given the high falsepositive of SMRP in a large-scale prospective study of SMRP for screening for ARDs in asbestos-exposed individuals [8], it is imperative to investigate the potential factors influencing the SMRP concentrations in subjects with a history of asbestos exposure.…”
Section: Introductionmentioning
confidence: 99%